Reorienting “Settled Identities”: Rethinking a Course on Jewish-Christian Relations - Boys, Mary C.; Schwartz, Shuly Rubin (Studies in Christian-Jewish Relations, 2022)
This article is a retrospective description and analysis of a course on Jewish-Christian relations offered jointly to students of Jewish Theological Seminary and Union Theological Seminary by a faculty member from each institution. The initial section lays out the fundamental contours of the course in 2020, with greater detail provided on the initial sections. The second explores areas in need of further refinement; a final section explores the potential of integrating threshold concepts, a way of opening new perspectives on topics, and proposes several such concepts that might guide future iterations of the course.